Meeting Place : The Human Encounter and the Challenge of Coexistence - Carter, Paul, 1951- (Book collections on Project MUSE., 2013)
In this book, the author explores the conditions for sociability in a globalized future. He argues that we make many assumptions about communication, but overlook barriers to understanding between strangers - as well as the importance of improvisation in overcoming these obstacles to meeting. While disciplines such as sociology, legal studies, psychology, political theory, and even urban planning treat meeting as a good in its own right, they fail to provide a model of what makes meeting possible and worth pursuing: a yearning for encounter. The volume's central narrative - between Northern cultural philosophers and Australian societies - traverses the troubled history of misinterpretation that is characteristic of colonial cross-cultural encounter. As he brings the literature of Indigenous and non-Indigenous anthropological research into dialogue with Western approaches of conceptualizing sociability, the author makes a startling discovery: that meeting may not be desirable and, if it is, its primary objective may be to negotiate a future of non-meeting. To explain the phenomenon of encounter, the author performs it in differing scales, spaces, languages, tropes, and forms of knowledge, staging in the very language of the book what he calls "passages." In widely varying contexts, these passages posit the disjunction of Greco-Roman and Indigenous languages, codes, theatrics of power, social systems, and visions of community. In an era of new forms of technosocialization, the author offers novel ways of presenting the philosophical dimensions of waiting, meeting, and non-meeting. --